2(6+3)=18-3(16-3d)

Simple and best practice solution for 2(6+3)=18-3(16-3d) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(6+3)=18-3(16-3d) equation:


Simplifying
2(6 + 3) = 18 + -3(16 + -3d)

Combine like terms: 6 + 3 = 9
2(9) = 18 + -3(16 + -3d)

Multiply 2 * 9
18 = 18 + -3(16 + -3d)
18 = 18 + (16 * -3 + -3d * -3)
18 = 18 + (-48 + 9d)

Combine like terms: 18 + -48 = -30
18 = -30 + 9d

Solving
18 = -30 + 9d

Solving for variable 'd'.

Move all terms containing d to the left, all other terms to the right.

Add '-9d' to each side of the equation.
18 + -9d = -30 + 9d + -9d

Combine like terms: 9d + -9d = 0
18 + -9d = -30 + 0
18 + -9d = -30

Add '-18' to each side of the equation.
18 + -18 + -9d = -30 + -18

Combine like terms: 18 + -18 = 0
0 + -9d = -30 + -18
-9d = -30 + -18

Combine like terms: -30 + -18 = -48
-9d = -48

Divide each side by '-9'.
d = 5.333333333

Simplifying
d = 5.333333333

See similar equations:

| 6+12=16 | | x+17=36-x | | x=20-0.5y | | 5=1-2n+5 | | 4(d-5)=1 | | 5m-14=8m+4 | | 2.5x-(-8.2)=26.7 | | -8n+4(1+5)=6n-14 | | -11(x+9)=99 | | 6x^4*3x^4= | | y=-0.80(55)+136 | | 4.3*p=28.81 | | 5n-9=71 | | 5(x+4)=75 | | 6y-7=10y+25 | | y=-0.80(45)+136 | | 7(1y+-2)+8=3(1y+-4)+-2 | | y=-0.80(35)+136 | | -18-6k=6(13k) | | 2x-1=-x+5 | | 15x^3-7x-2= | | x+29=83 | | 16/7=m/21 | | 3x+5=-6 | | 0.2x-1.5=0.1 | | 3a^2+4=0 | | 16-5(3t-4)=8-(-2t+11) | | -7(-5x+7)=-49 | | 4m-4=9m | | 29=17-2x | | 3y+5=y | | 6(-6x-10)=-132 |

Equations solver categories